Amelioration of Oxidative Stress in Rats with Chronic Obstructive Pulmonary Disease through Shenqi Huatan Decoction Activation of Peroxisome Proliferator-Activated Receptor Gamma-Mediated Activated Protein Kinase/Forkhead Transcription Factor O3a Signaling Pathway - Jingjing Chen; Wenxiao Qiao; Xiaoming Xue; Dian Li; Ye Zhang; Di Xie; Jinyun Wang; Yaoqin Sun; Shuo Yang; Zhuomin Yang (Canadian Respiratory Journal)
Background. Chronic obstructive pulmonary disease (COPD) is a common respiratory disease. Currently, no specific treatment strategy has been established; therefore, finding new treatment methods is essential. Clinically, Shenqi Huatan Decoction (SQHT) is a traditional Chinese medicinal formula for COPD treatment; however, its mechanism of action in treatment needs to be clarified. Methods. The COPD rat model was replicated by cigarette smoking and tracheal injection using the LPS method. The control group and the SQHT groups were treated with dexamethasone and SQHT by gavage, respectively. After treatment, superoxide dismutase (SOD) serum levels, total antioxidant capacity (TAOC), lipid peroxidation, and malondialdehyde (MDA) were detected by enzyme-linked immunosorbent assay (ELISA). Activated protein kinase alpha (AMPK-α), forkhead transcription factor O3a (FOXO3a), manganese SOD (MnSOD), and peroxisome proliferator-activated receptor gamma (PPARγ) were detected using reverse transcriptase quantitative polymerase chain reaction (RT-qPCR) and Western blot. Microribonucleic acid and protein expression levels were measured, and pathological changes in lung tissue were observed using hematoxylin and eosin staining. Results. The pathological findings suggested that SQHT substantially affects COPD treatment by enhancing alveolar fusion and reducing emphysema. ELISA results showed that SQHT could lower the blood levels of MDA and lipid peroxide and raise SOD and TAOC levels, suggesting that it could lessen oxidative stress. In the lung tissue of rats with COPD, large doses of SQHT intervention dramatically increased AMPK protein expression, AMPK-α, FOXO3a, MnSOD, and PPARγ, indicating that SQHT may reduce oxidative stress by activating the PPARγ-mediated AMPK/FOXO3a signaling pathway. Similar results were obtained using RT-qPCR. Conclusion. SQHT is effective for COPD treatment. The mechanism of action may be related to the activation of the PPARγ-mediated AMPK/FOXO3a signaling pathway to improve oxidative stress in lung tissue.